Operational safety: Development of electronic system for dynamic balance evaluation of farm tractors - Luciano, M. D. S. [UNESP]; Santos, J. E. G. [UNESP]; Santos Filho, A. G. [UNESP]; Cagnon, J. A. [UNESP]; Andreoli, A. L. [UNESP]; Arezes, P. M.; SantosBaptista, J.; Barroso, M. P.; Carneiro, P.; Cordeiro, P.; Costa, N.; Melo, R. B.; et al. (Crc Press-taylor & Francis Group, 2013)
The present study aimed at the development and evaluation of a low cost electronic device in order to provide safety for farm tractor users. The major accident occurrence in agricultural surroundings is from farm tractor side bending. Therefore, this sensor was designed to detect and alert about it. The results were satisfying.